Efektivitas Konseling Kelompok Teknik Self-Management Untuk Mengatasi Kesulitan Belajar Siswa SMP Negeri 1 Umbulsari - Nadiatul Fahiroh; Muhammad Fikri Fauzi; Faisol Hakim (Jurnal Ilmu Bimbingan dan Konseling, 2026)
Learning difficulties are commonly experienced by junior high school (SMP) students, particularly during the transition from elementary school. This study aims to examine the effectiveness of group counseling using the self-management technique in addressing learning difficulties among 7th-grade students at SMP Negeri 1 Umbulsari. A quantitative approach with a quasi-experimental Non-Equivalent Control Group Design was employed. The sample consisted of 20 students selected through purposive sampling — 10 in the experimental group and 10 in the control group. Data were collected using a learning difficulty questionnaire with 25 valid items (Cronbach Alpha = 0.893) and analyzed using an independent sample t-test. Results revealed a significance value of 0.017 (p < 0.05), indicating a significant difference between groups. The experimental group's posttest mean score (81.5) was higher than the control group's (74.8). Thus, group counseling with the self-management technique is proven effective in helping students overcome learning difficulties at SMP Negeri 1 Umbulsari.